Overlapping Authorities In Maritime Law Enforcement: A Case Study Of Ternate City - Ahmad Mufti; Faissal Malik; Fathurrahim Fathurrahim (Administrative and Environtmental Law Review, 2025)
The extensive legal framework governing maritime law enforcement in Indonesia has inadvertently created a proliferation of institutions with overlapping authorities and divergent jurisdictional interpretations, resulting in institutional silos that undermine coordinated operations and reduce enforcement effectiveness. Focusing on Ternate City’s waters, this research uses empirical legal research and descriptive qualitative analysis to examine these challenges and their implications, including the risk of inter-agency disputes and strained cooperation. It finds that six agencies—the Indonesian Navy, Bakamla, KPLP, the Directorate General of Customs and Excise, Polair, and PSDKP—exercise jurisdiction in the same maritime zones, generating complexity and confusion among stakeholders. Without clear coordination, enforcement becomes inefficient and potentially compromises national maritime security and economic interests. Therefore, a comprehensive strategy to harmonize mandates and strengthen inter-agency coordination is essential to ensure effective and cohesive law enforcement across Indonesian waters..